The Political Elitesâ€™ Response Discourse towards Prabowoâ€™s Speech Entitled â€œIndonesia Punahâ€ on Kompas.com and Republika.com - Sobari, Teti; Damayanti, Ema (Humaniora: Journal of Indonesia Culture and Society, 2021)
The background of research was developed by the responses of political elites to the statements of figures. The research problem was how the discourse of response and aligments from Prabowo speech entitled â€œIndonesia Punahâ€ published in Kompas.com and Republika.com, which were the material objects of the research. A qualitative approach combined with a descriptive analysis techniques were applied in the research. Analysis was done by using Michael Foucault`s power relation theory. The research indicates that Kompasâ€™ writing style tends to accentuate Jokowiâ€™s government side as a comparison in responding to Prabowoâ€™s speech. As for Republika, it dominates a clear description of the figure who gives the response. Then, the results of the power relations between Moeldoko and Hidayat Nur Wahid show that Moeldoko comments on behalf of the government by linking Jokowiâ€™s performance. Meanwhile, Hidayat Nur Wahid gives a response to save the reputation of the stigma embedded in him, namely the religious figure, deputy chairman of the People`s Consultative Assembly (MPR) of the Republic of Indonesia, and Prabowoâ€™s party bearer cadre.